THE RELATIONSHIP BETWEEN ONLINE GAMES ON SLEEP QUALITY IN ALDOLESCENT GIRLS AT SENIOR HIGH SCHOOL KARTIKA XIX-2 BANDUNG CITY - Az-zahrah, Mulia; Sriwenda, Djudju; Sofiyanti, Santi (HEARTY, 2024)
Games online can be accessed wherever and whenever . Playing games can make players happy, because it gives psychological satisfaction. The more interested in playing the game, the more time is spent to achieve pleasure. It can be said that someone is experiencing addiction if the individual is stopped from play will feel anxiety. This causes time to sleep to be used to play games as a result, a problem arises, namely sleep quality. The purpose of this study was to determine the relationship between online gaming and sleep quality in adolescent girls. This type of research is quantitative with a cross sectional approach. The population is teenage girls who play online games. The sampling technique used purposive sampling of 71 samples. The independent variable is online game addiction and the dependent variable is adolescent sleep quality. Data collection using the IAT and PSQI questionnaires. The univariate analysis test used descriptive statistics to see the distribution of age, duration of playing online games, online game addiction and sleep quality. The bivariate analysis test used Spearman rank correlation to see the relationship between online gaming and sleep quality. The results of univariate analysis of most adolescents' age are 16 years 40%, with the duration of playing online games for 3-6 hours / day 56.3%, who experience mild and moderate addiction equally 33.8%, who experience poor sleep quality 76%. The results of bivariate analysis using the spearman rank correlation test showed a p value of 0.03, with a coefficient coefficient of 0.345. There is a relationship between online gaming and sleep quality in adolescents. It is recommended to play online games < 3 hours / day from and parents can control play time management and sleep time. It is expected to continue this research by adding other variable factors that affect sleep quality in adolescents.